ChemInform Abstract: Reactivity and Selectivity of Donor Glycosides in Glycochemistry and Glycobiology: Trapped Covalent Intermediates. Issue 18 (11th April 2013) - Walvoort, Marthe T. C.; van der Marel, Gijsbert A.; Overkleeft, Herman S.; Codee, Jeroen D. C.
Abstract Review: 87 refs.